Funding Pension System of Russia in the Categories of National Accounts - Pasynkov, Aleksey Fyodorovich (Economy of Regions, 2018)
The ongoing changes in the pension system of Russia gave rise to a discussion about the degree of financial security of the pension rights, the ratio of «own» revenues and transfers of the federal budget to ensure payment of pensions. It ean be assumed that the ideas about the schemes and directions of financial support for the pension system of the Russian Federation that have been developed in modern literature and society are rather limited. Therefore, the main purpose of this study is a comprehensive assessment of the types and directions of expenditure for pensions in the Russian Federation, conducted from the perspective of their display in the System of National Accounts (SNA). The article generalizes the cost-determination principles for pension support for households within SNA as well as allocates basic differences in the forms of the pension system and their description in accounts of SNA. I have classified the types and sources of financial flows of the pension system in the Russian Federation as well as highlighted the channels and dynamics of the financing of pension liabilities. I have compiled the flows of the Russian Federation’s pension system depending on various sources: the Pension Fund of RF, law enforcement agencies, justice system, etc. On this basis, I have undertaken a comparative analysis of the key parameters for various sources of funding: the average pension, the burden of pension deductions for wages, the ratio of employed and retired people in various forms of the pension system. The research shows that in Russia, there are several forms of pensions, different in scale and sources of funding. Using uniquely the data of the Pension Fund of the Russian Federation for the analysis of properties of the pension system is incorrect from the point of view of both the basic principles of accounting of SNA flows and the real replacement of pensioner’s incomes. I prove that a significant part of the expenditure obligations for pension security is due the adoption by the government of increased social obligations, rather than a lack of income from the working population. The results of the research can be a basis for the calculation of pension liability in the Russian Federation.